2006
DOI: 10.1002/chin.200644270
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Free Energies of Enzymatic Reactions

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 233 publications
(402 reference statements)
2
30
0
Order By: Relevance
“…The PMF was obtained from a series of 35 umbrella sampling simulations for the reaction in water and 17 in the enzyme (4). Periodic boundary conditions were used along with the particle mesh-Ewald method (38) for the uncatalyzed reaction in a box of Ϸ30 ϫ 30 ϫ 30 Å 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PMF was obtained from a series of 35 umbrella sampling simulations for the reaction in water and 17 in the enzyme (4). Periodic boundary conditions were used along with the particle mesh-Ewald method (38) for the uncatalyzed reaction in a box of Ϸ30 ϫ 30 ϫ 30 Å 3 .…”
Section: Methodsmentioning
confidence: 99%
“…An intriguing, yet unanswered, question is whether enzymes have evolved to enhance tunneling to accelerate the reaction rate because quantum effects on rate acceleration are much smaller than hydrogen bonding and electrostatic stabilization of the transition state (1,4,5). Nevertheless, a small factor of two in rate enhancement can have important physiological impacts.…”
mentioning
confidence: 99%
“…Under some conditions, such as high temperature, extremes of pH or mechanical forces, protein will unfold into random coil that loses biochemical function (Selkoe 2003). Since folding and unfolding are essential to life, literatures on the study of these processes are very rich (Gao and Truhlar 2002;Gao et al 2006;Freddolino et al 2010;Yang et al 2010;Alhambra et al 2000;Duan et al 2010;Shank et al 2010). And it has been greatly advanced in recent years by the development of fast time-resolved techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, a connection between promoting motions and potential energy barrier modulation has never been demonstrated directly, and recent work has shown that the temperature dependence of kinetic isotope effects can be accounted for by conformational effects for a number of enzymes (5). Whereas some authors postulate dynamics as a key driving force in catalysis (1)(2)(3)(4), others have performed analyses showing activation free-energy reduction, which is an equilibrium property, to be the source of catalysis (6)(7)(8)(9)(10)(11)(12)(13)(14). Enzyme reactions, and particularly their dynamics, present formidable challenges for study, and progress requires a combination of theoretical, experimental, and computational approaches (5,(15)(16)(17)(18) (20).…”
mentioning
confidence: 99%